InterviewME: A comparative pilot study on M-learning and MAR-learning prototypes in Malaysian english language teaching - Cheng L.K.; Selamat A.; Alias R.A.; Puteh F.; bin Mohamed F. (Springer Verlag, 2023)
Artificial intelligence; Augmented reality; E-learning; Information systems; Motivation; Software prototyping; Teaching; Comparative studies; English as a second languages (ESL); English as second languages; English educations; English language teaching; Malaysian english; Mobile augmented reality; Mobile Learning; Computer aided instruction